The Cartography of Love in Doris Lessing’s “love, again” - Miroshnychenko, Lilia (Respectus Philologicus, 2020)
In her late novel, love, again (1996), Doris Lessing represents a penetrative insight of love, providing the widest perspective of love than in any of her previous work. The abundance and variety of plausible les affaires d’amour, which transgress the boundaries of gender, age, geography, and social status, make love, again Lessing’s most “loveful” novel. The narrative responds to this multiplicity accordingly. The essay explores the theme of romantic love of the central female character, Sarah Durham, who is at the centre of the narrative and whose emotional landscape is meticulously mapped. It also aims to unveil the ways Doris Lessing exploits a longstanding tradition of interpreting love in Western philosophy and culture – from Plato to contemporary theorists, including Alain Badiou. Special attention is paid to the interweaving of love and friendship in the relationship of woman and man as well as friendship’s “healing” power for unrequited love encapsulated in the character of Stephen Ellington-Smith. Also, by tracing the transformative impulse of love, the essay tries to bring light on the constructive (in the case of Sarah) and problematic (Stephen) consequences of love.
Keywords: Doris Lessing; interpretation of love; Stendhal; transgressive love; sensibility